2010
DOI: 10.3109/08923970903420582
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral vectors for immune cells targeting

Abstract: Lentiviral vectors are efficient gene delivery vehicles suitable for delivering long-term transgene expression in various cell types. Engineering lentiviral vectors to have the capacity to transduce specific cell types is of great interest to advance the translation of lentiviral vectors towards the clinic. Here we provide an overview of innovative approaches to target lentiviral vectors to cells of the immune system. In this overview we distinguish between two types of lentiviral vector targeting strategies: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 120 publications
0
27
0
Order By: Relevance
“…This enzyme transcribes the virus' RNA into a DNA sequence that the host cell machinery can transcribe and translate (Froelich et al, 2010).…”
Section: Recombinant Retroviral Vectorsmentioning
confidence: 99%
See 3 more Smart Citations
“…This enzyme transcribes the virus' RNA into a DNA sequence that the host cell machinery can transcribe and translate (Froelich et al, 2010).…”
Section: Recombinant Retroviral Vectorsmentioning
confidence: 99%
“…Retroviral vectors are capable of transducing a wide range of cell types, are able to accommodate extensive changes in their genome, accept long transgenes, have low immunogenicity, can be produced in high titers, and promote a prolonged transgene expression due to their ability to integrate into the host cell genome (Froelich et al, 2010). On the other hand, most retroviral vectors can only transduce replicating cells since the transport of the transcribed viral DNA to the nucleus is mitosis-dependent.…”
Section: Recombinant Retroviral Vectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…These phenotypically mixed particles, or pseudotypes, are constructed by incorporating heterologous glycoproteins onto the LV surface through the budding process in the producing cells (Cronin et al, 2005). The most commonly used Env glycoprotein of pseudotyped LVs is derived from vesicular stomatitis virus (VSV-G), which mediates viral entry through the binding of membrane phospholipids (Froelich et al, 2010;Giacca and Zacchigna, 2012), and a recent study showed that LDL receptor serves as the cellular receptors for VSV-G-pseudotyped LVs (Finkelshtein et al, 2013). Although VSV-G-pseudotyped LVs have broadened the range of infected cell types and possess good stability (Froelich et al, 2010), they also have some disadvantages, including toxicity of constitutive expression in producer cell lines and the susceptibility of inactivation by human complement (Ory et al, 1996;DePolo et al, 2000).…”
Section: Introductionmentioning
confidence: 99%